Strategies for Selecting Potentially Effective Biofumigant Species for Optimal Biofumigation Outcomes - Juan Manuel Arroyo; Jose Soler; Rubén Linares; Daniel Palmero (Agriculture)
Soil-borne diseases threaten sustainable agriculture, traditionally managed by chemical fumigants, whose use is now restricted due to environmental and health concerns. This study evaluates the biofumigation potential of Brassicaceae species, specifically Brassica carinata A. Braun., Brassica juncea (L.) Vassiliĭ Matveievitch Czernajew., Raphanus sativus L., and Sinapis alba L., cultivated in central Spain. Field trials across two growing cycles assessed biomass production, glucosinolate (GSL) concentration, photosynthetically active radiation (PAR) interception, and radiation use efficiency (RUE). Biomass production varied across species and sampling dates, with S. alba and R. sativus outperforming other species in shorter cycles, while B. juncea and B. carinata showed a more efficient GSL profile regarding soil-borne disease control, particularly in aliphatic GSLs like sinigrin. Results highlight B. juncea and B. carinata as potent biofumigants due to their high GSL levels, whereas S. alba and R. sativus are more suited to early biomass production. The study also explores the chlorophyll content index (SPAD) as a potential field indicator of GSL concentration, providing a practical approach for optimizing biofumigation timing. These findings support the selection of specific Brassicaceae species adapted to climatic conditions and crop cycles for effective biofumigation in sustainable agricultural practices.